Practices that are potential risks to an increase in zoonotic tuberculosis: A cross-sectional study among cattle holders in peri-urban area of Sonipat - Sonam Barak Lakra; Divya Aggarwal (Wolters Kluwer Medknow Publications, 2020)
Background: The main causative agents of bovine tuberculosis (TB) are Mycobacterium bovis and to a lesser extent, Mycobacterium caprae. The zoonotic transmission of these pathogens occurs primarily through close contact with infected cattle or consumption of contaminated animal products such as unpasteurized milk. Objectives: The objective of this study is to assess the association of practices potentially increasing the risk of zoonotic TB (zTB) among cattle holders in the peri-urban area of Sonipat district. Methodology: This study was carried out among 100 cattle holders. The snowball sampling method was used to select the study units. Those who were handling cattle at home for the maximum time were included under the study (one per household). Face-to-face interviews were carried out using a structured questionnaire. The modified Kuppuswamy scale was used for the segregation of risk. Results: Only 4% of participants have heard about zTB and belonged to the middle and upper-middle class. Dietary practices such as consumption of boiled milk and cooked meat, mixed type of milk, meat, and raw milk were found to be 15% (40-49 years), 68% (20-29 years), 3%, and 9% (30-39 years), respectively. Cooked meat was consumed by 15% of participants, of which 12% were of 20-29 years and 3% were of 30-39 years, whereas 3% (20-29 years) population was consuming mixed form of meat. Conclusion: The risky practices such as attending animal fares, treating sick cattle, and contact with stray animal and in dietary practices of milk and meat consumption increase the zTB risk.